2016
DOI: 10.1038/nenergy.2016.112
|View full text |Cite
|
Sign up to set email alerts
|

Potential for widespread electrification of personal vehicle travel in the United States

Abstract: Electric vehicles can contribute to climate change mitigation if coupled with decarbonized electricity, but only if vehicle range matches travelers' needs. Evaluating electric vehicle range against a population's needs is challenging because detailed driving behavior must be taken into account. Here we develop a model to combine information from coarse-grained but expansive travel surveys with high-resolution GPS data to estimate the energy requirements of personal vehicle trips across the U.S. We find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
148
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(160 citation statements)
references
References 37 publications
5
148
0
Order By: Relevance
“…The myriad of applications, technologies and locationspecific contexts that are absent from this cursory analysis can now be more readily explored in future studies. A recent study suggested EVs are suitable to replace the majority of vehicles in the US based on daily driving requirements 35 . To assess the economic competitiveness, we use ER analysis to project cost of ownership (in dollars per mile travelled) for the energy inputs and storage components of EVs (Nissan Leaf specifications) and conventional cars (see Methods and Supplementary Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…The myriad of applications, technologies and locationspecific contexts that are absent from this cursory analysis can now be more readily explored in future studies. A recent study suggested EVs are suitable to replace the majority of vehicles in the US based on daily driving requirements 35 . To assess the economic competitiveness, we use ER analysis to project cost of ownership (in dollars per mile travelled) for the energy inputs and storage components of EVs (Nissan Leaf specifications) and conventional cars (see Methods and Supplementary Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main causes that is currently limiting EV adoption is what is called range anxiety,which, among other factors, is determined by the infrastructure of the charging stations [24]. In order to deal with this problem, it is necessary to evaluate the set of possible configurations in order to offer a distribution of charging stations that satisfies the users and enhances the use of the EV.…”
Section: Proposal and Methodologymentioning
confidence: 99%
“…Travel surveys are an essential source for estimating real-world needs for the daily range for passenger car users. Examples of such studies can be found in Pearre et al [22] and Needell et al for North-American statistics [23]; and Pasaoglu et al [24] and Corchero et al [25] for European variants. These different sources confirm that most of the daily range needs are in the 0 to 80 km range, while ranges exceeding 150 km/day are found to occur only on a limited number of days per year, i.e., for only 5 percent of the daily trips [26,27].…”
mentioning
confidence: 99%